Norovirus-Specific Memory T Cell Responses in Adult Human Donors - Malm, Maria; Tamminen, Kirsi; Vesikari, Timo; Blazevic, Vesna (Frontiers in Microbiology, 2016)
Norovirus (NoV) is a leading cause of acute gastroenteritis in people of all ages worldwide. NoV specific serum antibodies which block the binding of NoV virus-like particles (VLPs) to the cell receptors have been thoroughly investigated. In contrast, only a few publications are available on the NoV capsid VP1 protein-specific T cell responses in humans naturally infected with the virus. Freshly isolated peripheral blood mononuclear cells of eight healthy adult human donors previously exposed to NoV were stimulated with purified VLPs derived from NoV GII.4-1999, GII.4-2012 (Sydney), and GI.3, and IFN-g production was measured by an ELISPOT assay. In addition, 76 overlapping synthetic peptides spanning the entire 539 amino acid sequence of GII.4 VP1 were pooled into two-dimensional matrices and used to identify putative T cell epitopes. Seven of the eight subjects produced IFN-g in response to the peptides and five subjects produced IFN-g in response to the VLPs of the same origin. In general, stronger T cell responses were induced with the peptides in each donor compared to the VLPs. A CD8+ T cell epitope in the shell domain of the VP1 (134SPSQVTMFPHIIVDVRQL151) was identified in two subjects, both having human leukocyte antigen (HLA)-A*02:01 allele. To our knowledge, this is the first report using synthetic peptides to study NoV-specific T cell responses in human subjects and identify T cell epitopes.